PETROCHEMISTRY AND GEOCHEMISTRY OF KIMBERLITES FROM DIFFERENT PROVINCES OF THE WORLD - Ilupin I.V.; Roshchina I.A. (My University, 2002)
This paper summarizes the data available on the concentrations of major and trace elements in kimberlites from various provinces of the world. Arithmetic means were calculated for individual kimberlite pipes and dikes, for groups of bodies from individual regions, and for the whole data sample. Some of the most interesting elements and ratios between them are compared and correlation coefficients are offered. Each of the objects of study was found to have its own petrochemical and geochemical characteristics. The kimberlites of the Gondwana group were found to be rich in K, P, La, Th, Zr, and Nb and poor in Ca. Some of the patterns established for the kimberlites of Siberia appeared to be common for all kimberlites, this suggesting some common trend of the deep material evolution during the formation of kimberlite magma and its rise to the ground surface.
Keywords: KIMBERLITE; PETROCHEMISTRY; GEOCHEMISTRY; CORRELATION